2021
DOI: 10.3390/nu13041049
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Influences Membrane Fusion during Myogenesis by Modulating Oxidative Stress in C2C12 Myoblasts

Abstract: Magnesium (Mg) is essential to skeletal muscle where it plays a key role in myofiber relaxation. Although the importance of Mg in the mature skeletal muscle is well established, little is known about the role of Mg in myogenesis. We studied the effects of low and high extracellular Mg in C2C12 myogenic differentiation. Non-physiological Mg concentrations induce oxidative stress in myoblasts. The increase of reactive oxygen species, which occurs during the early phase of the differentiation process, inhibits my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…In the muscle of hypomagnesemic mice, a significant downregulation of Mg transporters has been observed. Moreover, we demonstrated that Mg is required to accomplish myogenic differentiation and membrane fusion since non-physiological extracellular Mg concentrations impact the myoblasts ability to fuse and form multinucleated cells [6]. Nonetheless, very little remains known about Mg homeostasis and its transporters in myogenesis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the muscle of hypomagnesemic mice, a significant downregulation of Mg transporters has been observed. Moreover, we demonstrated that Mg is required to accomplish myogenic differentiation and membrane fusion since non-physiological extracellular Mg concentrations impact the myoblasts ability to fuse and form multinucleated cells [6]. Nonetheless, very little remains known about Mg homeostasis and its transporters in myogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…It has been proposed that Mg might play a role in the myogenic process since Mg deficiency enhances the expression of the myogenic proteins Myogenic Differentiation 1 (MyoD) and Myogenin (Myog) in rat skeletal muscle [5]. Moreover, we have recently demonstrated that non-physiological low or high extracellular Mg concentrations inhibit myogenesis in C2C12 myoblasts, through an ROS-mediated impairment of membrane fusion [6].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This is not surprising since magnesium is key for all the enzymes utilizing or synthesizing muscle ATP, and thus for the production of muscle energy, and also regulates contraction and relaxation [ 25 ]. Additionally, magnesium assures the regenerative capacity of skeletal muscle fibers [ 91 ].…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium also has a fundamental role during myogenesis. Non-physiological magnesium concentrations induce oxidative stress in myoblasts, and this oxidative stress is responsible for the inhibition of myoblast membrane fusion, thus impairing myogenesis [ 11 ]. Magnesium also affects bone growth and remodelling.…”
mentioning
confidence: 99%